Organizational Pathology Compared to What? Impacts of Job Characteristics and Career Trajectory on Perceptions of Organizational Red Tape. - Ponomariov, Branco L.; Boardman, P. Craig (Public Administration Review)
Early studies of organizational red tape emphasized that worker perceptions of organizational rules and procedures are dependent on workers’ frames of reference. However, most prior studies do not account sufficiently for how and why these reference points vary across employees, even if they work within the same or similar organizational contexts. While the effects of contemporaneous employee attitudes on perceptions of red tape have been considered in prior analyses, how do perceptions of organizational rules and procedures as red tape relate to workers’ prior career trajectories and occupational contexts? Variable norms and expectations across organizations as well as across the public and private sectors may produce different attitudes toward rules and procedures. Of equal import, current occupational characteristics are relatively unexamined in studies of worker perceptions of red tape. Using a survey of state level public managers, this paper examines how employees’ perceptions of red tape are mediated by their prior career trajectories and experiences, as well as by their occupational context. Implications for theory and practice are discussed.